Alum: an efficient catalyst for one-pot synthesis of alpha-aminophosphonates - Sonar, Swapnil S.; Shelke, Kiran F.; Kakade, Gopal K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
Alum (KAl(SO(4))(2)center dot 12H(2)O) is an inexpensive, efficient, non-toxic and mild catalyst for the one-pot synthesis of alpha-aminophosphonates. A three component reaction of an aldehyde/ketone, an an-tine and triethyl phosphite was carried out under solvent-free conditions to afford the corresponding alpha-aminophosphonates in short reaction times and high yields with the green aspects by avoiding toxic catalysts and solvents. (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Aldehyde/ketone; alpha-Aminophosphonates; Alum; Amine; Solvent-free; Triethyl phosphite